Strategi Humas Bella House Of Beauty Dalam Meningkatkan Brand Awareness Melalui Instagram - Putri Rahayu; Tira Fitriawardhani; Julyanto Ekantoro (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
In the digital era, social media has become a strategic tool for businesses to build competitive advantage and enhance brand awareness, including in the beauty industry. Instagram is widely utilized due to its large number of users and strong visual characteristics in shaping brand image. This study aims to analyze the public relations strategy of Bella House of Beauty in increasing brand awareness through Instagram. The research employs a qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that Bella House of Beauty optimizes various Instagram features, such as feeds, stories, and reels, as media for information delivery, promotion, and entertainment. In addition, collaborations with local media and influencers are implemented to expand audience reach. These strategies are considered effective in improving brand awareness, as reflected in the increase in viewer numbers and audience interactions on the Bella House of Beauty Instagram account.